The categories of Arabic prepositon and Kazakh case: A Contrastive analysis - Т., Ниномия; С., Борaнкуловa (Journal of Oriental Studies, 2019)
This study is based on preliminary contrastive analysis of the Arabic prepositions and cases of the Kazakh language. The purpose is to find out the similarities and differences between two languages. e found not only the regular correspondents (e.g., Arb. ’ilaa / Kaz. O3; Arb. fii / Kaz. O5; Arb. min / Kaz. O6), but also the following irregular correspondents: (1) Arb. ’ilaa, li/ Kaz. O4; (2) Arb. accusative case / Kaz. O3; (3) Arb. bi, min, ‘an / Kaz. O3, O4; (4) Arb. ‘alaa / Kaz. O4, for + the name of the case; (5) Arb. fii / Kaz. O3, O4, O6, for + the name of the case, about+ the name of the case. The preposition fii of Arabic showed the most complicated correspondent in the Kazakh language (e.g., šakka fii A: A(O3) doubt; istamarra fii A : A (O4) continue; ’axṭa’a fii A: A (O6) make mistakes; jaahada fii A : A (1) fight for; jaadala fii A : A (1) argue about). These complex patterns are a useful list for the Kazakh learners of Arabic. The previous studies have not shown many and detailed correspondences in this field. Key words: Arabic, Kazakh, case markers, preposition.